Testicular ascent as a mechanism for intra-abdominal torsion - Plitt, David C. (Radiol Case Rep, 2015)
Testicular ascent, while uncommon, can occur. A testicle that has ascended out of the scrotum can torse and may present as an acute inguinal mass or acute abdomen. Testicle ascent can occur even if previous intra-scrotal location has been documented.